Analisis Permainan Sepak Bola: Pola Menyerang, Bertahan dan Transisi Timnas Indonesia U-19 Vs Bulgaria - Wibowo, Herlambang Fajar; widiyanto, Widiyanto; Nugroho, Mahir Dwi (Journal of Sport Science and Education, 2021)
The aim of this research is to analyze the game patterns of the U-19 Indonesian National Team and can be an inspiration and reference for football coaches and staff, especially in paying attention to game patterns. This is a qualitative research using the observation method. Data were collected through non-participant observation. The results showed the game patterns of the U-19 Indonesian National Team when doing defensive, attacking and transition moments. When defending, the national team did a defensive moment with a low zone with a 1-4-4-2 formation with flat technique. For attacking moment, they did a build up attack or build up from the goalkeeper to the front. For transition moments of attacking to defend they carried out a pattern of returning to the position zone, and for a moment of transition to defending to attacking they carried out a counterattack strategy.  In this study, it was found that a lack of determination by Indonesian national team players in implementing a negative transition strategy that to be late to return to base, it is advisable to increase the physical condition of the players with different training methods, because the physical condition needs of soccer players vary depending on position.